Answer:
![\begin{equation*} g(d)-f(d)=-d^2-d-2 \end{equation*}](https://img.qammunity.org/2023/formulas/mathematics/college/t1qepvx6lbtff6ohvo1qcri8kylkv1zpy8.png)
Step-by-step explanation:
Given:
![\begin{gathered} f(x)=x^2+4 \\ g(x)=-x+2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dz1219yqviaesfldgyczo6b7lwabckj47x.png)
To find:
![g(d)-f(d)](https://img.qammunity.org/2023/formulas/mathematics/college/b5so7ivr74k49hnbvcu2ft47ckwt537g08.png)
We can find g(d) by substituting x in g(x) with d, so we'll have;
![g(d)=-d+2](https://img.qammunity.org/2023/formulas/mathematics/college/ajs7rwq0b49399f2jf7wf29m9dke0pl61f.png)
We can find f(d) by substituting x in f(x) with d, so we'll have;
![f(d)=d^2+4](https://img.qammunity.org/2023/formulas/mathematics/college/8ppu84g4g5qxk2uhou7bth175c1jai3hsh.png)
We can now go ahead and subtract f(d) from g(d) and simplify as seen below;
![\begin{gathered} g(d)-f(d)=(-d+2)-(d^2+4)=-d+2-d^2-4=-d^2-d+2-4 \\ =-d^2-d-2 \\ \therefore g(d)-f(d)=-d^2-d-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/9wj1bw3mch4ybxwk99kguch3spdizjoe5r.png)
Therefore, g(d) - f(d) = -d^2 - d -2